Book Review Essay: The Environmental Crisis and Its Capitalist Roots: Reading Naomi Klein with Karl Polanyi*—Naomi Klein: This Changes Everything: Capitalism vs. the Climate - Adler, Paul S. (Administrative Science Quarterly, 2015)
An essay is presented on the relationship between climate change and capitalism, offering a reading of the argument in "This Changes Everything: Capitalism vs. the Climate" by Naomi Klein through the lens of the analysis in "The Great Transformation" by Karl Polanyi. The author suggests that Klein's argument is not clear on whether capitalism in any form or only the current, neoliberal version of capitalism is incompatible with effective action to address the problem of climate change. Topics include environmental externalities and policies addressing them, the environmental record of corporations, and the theory of the self-regulating market.
Business; Management Studies; Administrative Science
Keywords: Great Transformation; The (Book); KLEIN; Naomi; This Changes Everything (Book); business enterprises & the environment; capitalism; climatic changes; economic aspects; environmental policy; externalities

Corporate Power and Responsible Capitalism?: Towards Social Accountability - Jones, Bryn (Edward Elgar Publishing, 2015)
In this important book, Bryn Jones uses insights from political economy, historical analysis and sociological concepts of the corporation, as a socially disembedded but political actor, to address concerns over the over-reach of Anglo-Saxon corporation KM – on page 6: "Following Karl Polanyi, I argue that ST/EM firms have outgrown and threaten to dominate, envelop and even undermine, some of the social and political institutions on which a sustainable market economy depends. Any rebalancing of the relationship between corporations and the rest of society must therefore interrogate the nature of the relationship between market organisations, such as firms, and the social institutions to which they are linked.
Economics; Business Studies
Keywords: ST/EM corporations; business & economics; business ethics; business systems; corporate governance; disembedding; executive managed corporations; industrial management; management; management science; organizational behavior; share-traded corporations; social embedding

Mobilizing the depths of the market: Motivation research and the making of the disembedded consumer - Schwarzkopf, Stefan (Marketing Theory, 2015)
Twentieth-century consumer society was characterized by a process of disembedding as described by Karl Polanyi in The Great Transformation (2001 [1944]). The Austro-American consumer researcher Ernest Dichter played a key role in preparing the ideological framework necessary for this process to succeed. In order to assess Dichter’s role and that of psychoanalytic motivation research in general in the creation of the idea of the disembedded consumer, this article presents an analysis of Dichter’s unpublished consumer research reports ranging across different countries and industries between 1939 and 1973. Through content analysis and historical contextualization, I show that Ernest Dichter in particular and psychoanalytic motivation research in general were instrumental in removing from market relationships the invisible hand of social norms. The case of the consumer psychoanalyst Ernest Dichter thus provides new insights into the sociocultural mechanisms by which theorizing in consumer research can influence the objects of its theorizing.
Business; Marketing
Keywords: DICHTER; Ernest; consumer research; disembedding; interpersonal relations; market society; marketing; motivation research; pleasure principle; psychoanalysis; therapeutic ethos